Comparing perceptions of mathematics: Norwegian and Finnish university students‘ definitions of mathematics - Vähämaa, Miika; Härmälä, Kennet (NOMAD Nordic Studies in Mathematics Education, 2011)
The article presents a comparison between Norwegian and Finnish university students’ perceptions of what mathematics is. To carry out the comparison, a mix of qualitative - the creation of abstract and concrete categories for mathematics representations - and quantitative (regression modeling) methods was used in the study. The main result of the study is that Norwegian students were more homogenous in their responses and the vast majority perceived mathematics in concrete terms. The Finnish students, on the contrary, showed greater variety in their responses. There are not many comparative studies among Nordic countries regarding students’ perceptions of mathematics. Therefore this study contributes to improving our knowledge about the possible differences and similarities on students’ perceptions of mathematics among Nordic students. A total of 239 students were asked how they perceive mathematics, numbers and personal applicability of mathematics via an open questionnaire. We propose that the divergent perceptions of mathematics stem from different types of communication cultures that surround mathematics. The argument is made that perceptions of mathematics should be treated as a type of mathematical knowledge that is valuable whenever mathematics is communicated.